IN VIVO AND IN VITRO STUDIES ON STIGMASTEROL ISOLATED FROM PEDALIUM MUREX - PRIYANKA SHARMA,; RENU SARIN, (International Journal of Pharma and Bio Sciences, 2012)
In the present study, stigmasterol has been reported from Pedalium murex L. of pedaliaceae family in vivo and in vitro. Quantification data revealed that the total sterol content was higher in callus than leaves. The in vitro studies showed that the maxmium amount of total sterol was found in 6 weeks old tissue and minimum in 2 weeks old callus culture. In vivo studies showed that higher content of sterol was in leaf and lower in stem. The present investigation was aimed to investigate stigmasterol present in P. murex. Stigmasterol was isolated from various plant parts and callus cultures of Pedalium murex and was identified using TLC, GC-MS, mp, IR, and UV studies, which was comparable to that of the standard stigmasterol.